ABOUT LITERARY PROCESS OF 90th … AND NOT ONLY Yevgen Baran. Ninetieth inside out: essay / Ye.M. Baran. – Ivano-Frankivs’k: Suprun V.P., 2011. – 172с. - Khorob , M. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The review of book of essayistic modern literary critic Yevgen Baran contains the reflections not only about written by a literary critic but also about responsibility (professional and moral) of critic.